2011
DOI: 10.1007/s00221-011-2637-8
|View full text |Cite
|
Sign up to set email alerts
|

Force control deficits in chronic stroke: grip formation and release phases

Abstract: The aim of the study was to develop a novel approach for quantifying stair-stepping in a trajectory tracking task with the goal of understanding how age and stroke-related differences in motor control contribute to force control deficits. Nine stroke participants, nine age-matched controls, and nine young healthy adults performed an isometric gripping task while squeezing, holding, and releasing a cylindrical device. The visual tracking task involved three different rates of force production (5, 10, and 20% ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 68 publications
6
46
0
Order By: Relevance
“…Very few studies exist that compare young and older adults during force increase and release. Specifically, there is a single study that suggests exacerbation of force variability during force release in older adults relative to young adults (Naik et al 2011). Nonetheless, the gain of visual feedback and rate of force development was not controlled in that study, which could influence the results.…”
Section: Age and Force Variabilitymentioning
confidence: 97%
See 1 more Smart Citation
“…Very few studies exist that compare young and older adults during force increase and release. Specifically, there is a single study that suggests exacerbation of force variability during force release in older adults relative to young adults (Naik et al 2011). Nonetheless, the gain of visual feedback and rate of force development was not controlled in that study, which could influence the results.…”
Section: Age and Force Variabilitymentioning
confidence: 97%
“…For instance, participants exhibited altered force control during a power grip task while releasing force than increasing force (Naik et al 2011). This finding seemed to be independent of the participant's age or rate of force generation.…”
mentioning
confidence: 89%
“…To assess these motor abilities, various submaximal force-matching tasks and computational methods have been developed (Lodha et al 2010(Lodha et al , 2012Naik et al 2011;Lindberg et al 2012;Kang and Cauraugh 2014). Recently, a hierarchical variability decomposition (HVD) model was developed for the purpose of quantifying specific motor abilities that contribute to the motor behaviors of a redundant motor system (Koh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although various motor abilities are required in steady force production tasks, the motor control deficits after stroke have been typically captured through a few indexes such as the steadiness of the finger force (Kurillo et al 2004;Lodha et al 2010Lodha et al , 2012Naik et al 2011;Lindberg et al 2012;Chang et al 2013). Other motor abilities such as accuracy, reproducibility, flexibility, or multiformity are not well understood in the stroke population, although one previous study reported that stroke survivors retained multiformity in reaching tasks (Reisman and Scholz 2003) while still showing deficits in reproducibility (Reisman and Scholz 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Its clinical effectiveness has been well studied in other conditions, such as stroke [17][18][19], Parkinson disease [18,20], brain injury [14,21], and chronic inflammatory demyelinating polyneuropathy (CIDP) [19]. The target tracking test visualizes a predefined waveform that a subject must track by adjusting handgrip force in order to minimize the error between the waveform and the subject's response.…”
Section: Introductionmentioning
confidence: 99%